المرشد السياحي المحلي ودوره في تعزيز التنمية السياحية المستدامة "دراسة تطبيقية على محمية منتزه وادي الكوف/ ليبيا" (Comprehensive Journal of Science, 2025)
The tour guide plays a pivotal role in enriching the visitor experience and enhancing the positive image of tourist destinations. Their contribution is an important factor in supporting sustainable tourism development through cultural promotion and stimulating tourism spending. The problem of the study was to strengthen the relationship between the local tour guide and the local community for the benefit of spatial tourism in the Wadi Al-Kuf Reserve. Therefore, this study aimed to demonstrate the role of the tour guide in promoting sustainable tourism development. The researchers followed a descriptive analytical approach to describe the situation and extract its results through a personal interview conducted with a sample of (7) tour guides. The study reached several conclusions and recommendations that stakeholders are encouraged to consider.
Keywords: Tourism awareness, ecotourism, tourism experience, environmental balance, community involvement